SYNTHESIS OF NITROGEN CERAMIC POWDERS BY CARBOTHERMAL REDUCTION AND NITRIDATION .3. ALUMINUM NITRIDE - CHO, YW; CHARLES, JA (INST MATERIALS, 1991)
It has been found that the reaction rate between alumina and carbon in nitrogen can be considerably increased by using Al(OH)3-C mixtures instead of alpha Al2O3-C mixtures. The C/Al(OH)3 ratio in the starting mixtures should be greater than the stoichiometric ratio to complete the reaction. It was observed that alumina is reduced and nitrided to form aluminium nitride via spinel type aluminium oxynitride which is an intermediate compound. The overall reaction rate increased with decreasing Al(OH)3 particle size and increasing nitrogen flowrate. It is thought that the faster reaction rates obtained from Al(OH)3-C mixtures were derived from the high specific surface area of transition aluminas, such as gamma Al2O3, which formed during heating of the samples to the reaction temperature. The particle morphologies of the Al(OH)3 powders did not change during the reduction and nitridation reaction, an important attribute to the process.
Keywords: HIGH-THERMAL-CONDUCTIVITY; FINE AIN POWDER; ALN; SUBSTRATE; FILM